How to correct the impact of ethnicity on effectiveness of the second trimester maternal serum screen of fetal Down syndrome?. (18th October 2019) - Tana, Chonthicha; Wanapirak, Chanane; Sirichotiyakul, Supatra; Tongprasert, Fuanglada; Srisupundit, Kasemsri; Luewan, Suchaya; Sekararithi, Ratanaporn; Tongsong, Theera
Abstract: Objectives: To compare the performance of second trimester maternal serum screen (MSS) for fetal Down syndrome in Thai population between the conventional method using Caucasian reference ranges with ethnic factor correction (CRR-EC) and the method using specific Thai reference ranges (TRRs). Methods: A prospective database of the MSS project was accessed. The concentrations of alpha fetoprotein (AFP), beta-hCG, and uE3 were converted to their multiple of medians (MoMs) by two methods; CRR-EC for Asian women and TRR. The detection rate and false positive rate derived from the two methods were compared. Results: Of 20, 229 cases, 35 women had fetal Down syndrome. The detection rates of both methods were comparable, whereas the false-positive rate of TRR was significantly lower (8.8 versus 11.7%; p < .001). The improvement was mainly caused by more accuracy of the MoMs of beta-hCG, not AFP/uE3, based on TRR. Conclusions: The effectiveness of MSS could be improved by using our own reference ranges instead of using ethnic factor correction. With TRR, the false-positive rate or the number of invasive diagnoses could be significantly decreased without compromise of the detection rate. To improve MSS performance, each population should use its own reference ranges.